ALAT PEMESANAN NOMOR BANGKU BIS TERINTEGRASI SECARA WIRELESS - Susila, Tjandra; Winata, Tony; Trimamangsyah R., Trimamangsyah R. (Universitas Tarumanagara, 2007)
Ticket order officer send information about seat number ordering from bus station to bus agency or the other hand. In one unit, the officer push a keypad and then the LED in the unit will â€œONâ€. Beside that, he also transmitt the message to the other unit. When the other unit receive the message, the LED in the unit will â€ONâ€. So, with this seat number order instrument the passenger can get their seat number faster and efficiently.